(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
The Katsina central market in Nigeria’s Katsina State is where sixteen soaps were purchased. The following physicochemical parameters were used to evaluate the soaps: pH, Total fatty matter (TFM), M&V, Alcohol insoluble (AI), Free alkali (FA), and Alcohol insoluble (AI). Typically, the following soap samples fail the tests: TFM 25%, AI 75%, FA 50%, pH 50%, M&V 100% for laundry soaps; TFM 50%, AI 100%, FA 75%, pH 50%, M&V 100% for toilet soaps; and TFM 25%, AI 75%, FA 75%, pH 0%, and M&V 75% for medicated soaps. According to the chemical analysis of this study, 61% of the laundry, toilet, and medicated soaps offered in Katsina metropolis are subpar, counterfeit, and not real, based on the Standard Organization of Nigeria (SON) recommended values. The conclusion is that while many soaps are of poor quality, only a small number of them are genuine, which could be harmful to people’s health. The relevant authorities must impose tight regulations to guarantee the manufacturing of high-quality, consumer-safe soaps.